LGBT community in Ukraine: reality - Войтовська, А. І. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2018)
Analysis of tendencies of gender identity in society.The current state of the LGBT movement (lesbian, gay, bisexual and transgender people) in Ukraine with an emphasis on features of the national law enforcement in this area.Deals with political relations in Ukraine to members of the LGBT community. The results of the expert poll among students of Uman State Pedagogical University named after Pavlo Tychyna.